Perbandingan Instalasi Pengolahan Air Limbah Pada Hunian Tipe RSS (Rumah Sangat Sederhana) : Studi Empiris Perumahan Green Barusuda Indah - Adi Susetyaningsih; Muhamad Andhika Abdul Azis (Institut Teknologi Garut, 2026)
Domestic wastewater management is an important challenge in housing development, particularly in areas consisting of RSS-type housing (Very Simple Houses) occupied by low-income communities. In regions that do not yet have urban wastewater treatment systems, alternative technologies are required that are efficient, economical, and compatible with the financial capabilities of residents. This study aims to analyze the comparison between Independent Wastewater Treatment Systems (IPAL Mandiri) and Communal Wastewater Treatment Systems (IPAL Komunal) based on aspects of construction cost, maintenance, and sustainability. The study was conducted in the Green Barusuda Indah Housing Complex, Cigedug District, Garut Regency, which consists of 69 housing units of type 36/60 equipped with an Independent IPAL system. Based on SNI 2398:2017 guidelines and the Regulation of the Minister of Public Works and Public Housing No. 4 of 2017, residential areas with more than 50 housing units are recommended to use a Communal IPAL system. The research employed a descriptive quantitative method with a comparative approach to assess the technical, economic, and operational efficiency of both systems. The results indicate that the Communal IPAL system is more efficient and sustainable, with a construction cost of only IDR 95.96 million, significantly lower than the Independent IPAL system, which requires IDR 417.84 million. Over a 20-year period, the maintenance cost of the Independent IPAL system reaches approximately IDR 1 billion, whereas the Communal IPAL system requires only around IDR 400 million. Therefore, the Communal IPAL system is more suitable for densely populated residential areas because it is more cost-effective, efficient in management, and supports environmental sustainability through community participation.